Activity Space, Neighborhood Built Environment, and Physical Activity: A Pilot Study from a Rural Community in the Lao People's Democratic Republic. (June 2018) - Jiang, Hongwei; Pongvongsa, Tiengkham; Yonto, Daniel; Moji, Kazuhiko; Lin, Lin
Abstract : Background: Studies that used activity space to assess built environmental exposure have gained increasing popularity in public health research. However, all those studies were conducted only in urban areas in developed countries. Rural residents have different activity patterns than their counterparts in urban areas. Furthermore, experts in physical activity have launched a call for studies from developing countries recently. Limited studies conducted in urban areas from developing countries have been published in international public health journals. Yet, studies on rural residents in developing countries are still lacking. This study is to fill this research gap by investigating the association of activity space, neighborhood built environment, and physical activity of rural residents in the Lao People's Democratic Republic. Methods: Five waves of surveys were conducted in Songkhon district, Savankhet province, Laos in March 2010, June 2010, September 2010, December 2010, and March 2011, respectively. Adults aged between 18 and 65 were recruited. For each wave, portable GPS (Holux M241) was used to record activity and farmland locations of participants; accelerometer (Lifecorder EX, Suzuken Ltd.) was used to record participant's physical activity level; and self-reported day-time activity log was recorded for seven consecutive days. Each participant who completed one wave of survey was given 20000 Lao kip (USD2.5), and a total of USD 12.5 (100, 000 Lao kip) was given to participants who completed five waves of surveys. Neighborhood built environment attributes were derived from google map. Spatial statistical analysis was employed to investigate the association between activity space, neighborhood built environment, and physical activity. Preliminary Results: There were 30 participants recruited at the first wave of the survey, and 70% of those initial participants (21 participants) completed five waves of surveys. About half of those initial 30 participants were women. The duration of physical activity for men was significantly longer than their female counterparts. We also found that the radii of activity space variated by month. The activity space radii in March and June were bigger than that of September and December. Conclusions: This is one of the first studies examining the association among activity space, neighborhood built environment, and physical activity in a developing country.